Building and Growing a Hospital Intranet: A Case Study - Ong, Kenneth R; Polkowski, Michelle; McLemore, Geoff; Greaker, Mark; Murray, Malcolm (JMIR Publications, 2001)
BackgroundThe Intranet is a rapidly evolving technology in large hospitals. In this paper, we describe the first phase of an Intranet project in a multi-hospital system in New York City. Objectives(1) To encourage the use of the Intranet among physicians, nurses, managers, and other associates in a multi-hospital system; and (2) to build the Intranet in a cost-effective manner using existing resources. MethodsA WebTrends Log Analyzer assessed the Intranet use in terms of the number of accesses from each department. ResultsA broad range of features, including medical knowledge resources, clinical practice guidelines, directions, patient education, online forms, phone directory, and discussion forums were developed. Analysis of more than 890,000 hits revealed the departments with hits greater than 1,000 were the 'Library' (6,130), 'Physicians Gateway' (2,539), 'Marketing' (1,321), 'Information Systems' (1,241), and 'Nutrition' (1,221). Of 819 unique visitors, 74 per cent visited more than once. ConclusionsIt is possible to create and diffuse an Intranet in a multi-hospital system in a cost-effective manner. However, the key challenges were selling the potential of this new technology to opinion leaders and other stakeholders, and converting pre-existing printed content by obtaining word processed and image files from other departments or contracted print publishers.